Exploring the potential of human dental pulp stem cells for treatment of retinal degeneration in Sprague Dawleyrat Model - Alsaeedi, Hiba Amer (2018)
Blindness and vision impairment are caused by irremediable retinal degeneration in affected individuals worldwide. Cell therapy for a retinal replacement has the potential to rescue their vision, specifically for those who lost most or all the light sensing photoreceptors in the eye. As such, well-characterized retinal cells are required for the replacement purposes. Stem cell-based therapy has been well received for retinal pigment epithelium and photoreceptor transplantation in the eye, however, the drawbacks of retinal transplantation is the limited clinical protocols development, insufficient number of transplanted cells for recovery, the selection of potential stem cell sources that can be differentiated into the target cells, and the ability of cells to migrate into the host tissue. Dental pulp stem cells (DPSC), a type of mesenchymal stem cells, are recently being studied due to its high capability of differentiating into cells of the neuronal lineage. Therefore, the main objective of the current study is to assess the potential of dental pulp stem cells therapy for ocular disorder in the Sprague-Dawley rat eye model. hDPSCs were cultured expanded and assessed for their mesenchymal stemness in-vitro. About 300.000 of DPSCs were transplanted intravitreal into the right eye of the rat retina n = 3. Moreover, the function of the retina was recorded by assessing the a- and b- wave amplitudes of ERG. Structural changes and protein expression were determined through IHC staining. The findings of the current study demonstrated that the transplanted hDPSCs slowed down the retinal degeneration progression and protected retinal functions for up to 4 weeks and according to the following results, (1) the visual functions level of the treated retina with hDPSCs were comparably better than the control, (2) the b-wave amplitude was higher compared to control at day-40, (3) no formation of tumor was observed in the retinal tissue, (4) the protein expression of the RHO and RPE65 was highly observed in the treated retina compared to the control. In conclusion, my results suggested that hDPSCs are an effective source for retinal degeneration therapy, and intravitreal injection boosts the therapeutic effect of hDPSCs.